Fuzzy variable structure control of dynamical systems with an application to micro satellite stabilization - Rusli, R.; Nagarajan, Ramachandran, Prof. Dr.; Muhajir, Rahim; Zuraidah, Md. Zain, Prof. Dr. (Institute of Electrical and Elctronics Engineering (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/